2016
DOI: 10.1093/rheumatology/kev436
|View full text |Cite
|
Sign up to set email alerts
|

LowC4,C4AandC4Bgene copy numbers are stronger risk factors for juvenile-onset than for adult-onset systemic lupus erythematosus

Abstract: Low total C4, C4A and C4B GCN were associated with a stronger risk for developing JSLE than aSLE. Additionally, low total C4 and C4A GCN are risk factors for pericarditis in JSLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…The present study confirmed, also in the peculiar blended Brazilian ethnicity, the association between low total C4 and C4A GCN and adult SLE previously reported in other ethnicities [7][8][9], and expanded this concept to low C4B GCN. This result corroborates a previous study with 90 patients with juvenile SLE and 170 patients with adult-onset SLE in Brazilian population, which showed a strong association with low number of copies of C4, C4A and C4B with SLE, remarkably in juvenile-onset lupus [26]. In addition, the present study originally demonstrated the impact of a lower C4A GCN on the progression of the disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study confirmed, also in the peculiar blended Brazilian ethnicity, the association between low total C4 and C4A GCN and adult SLE previously reported in other ethnicities [7][8][9], and expanded this concept to low C4B GCN. This result corroborates a previous study with 90 patients with juvenile SLE and 170 patients with adult-onset SLE in Brazilian population, which showed a strong association with low number of copies of C4, C4A and C4B with SLE, remarkably in juvenile-onset lupus [26]. In addition, the present study originally demonstrated the impact of a lower C4A GCN on the progression of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…While the association between low C4 GCN and SLE has been consistently demonstrated, the impact of C4 CNV on the disease phenotypes remains controversial. In our previous study in juvenile-onset SLE, the low GCN for total C4 and C4A was associated with pericarditis [26]. A study in Chinese Han patients reported an association between low C4A deficiency and arthritis [7], while a more recent study reported serositis as the only clinical manifestation associated with low C4A GCN [17].…”
Section: Discussionmentioning
confidence: 89%
“…A recent research showed that low total C4, C4A, and C4B gene copy number (GCN) were associated with a stronger risk for developing cSLE than adult SLE. Additionally, low total C4 and C4A GCN were risk factors for pericarditis in cSLE patients [13].…”
mentioning
confidence: 91%
“…[32] In addition, deficiencies in components of the complement system are prone to develop SLE. [33] …”
Section: Discussionmentioning
confidence: 99%